Carboxylic and O-acetyl moieties are essential for the immunostimulatory activity of glucuronoxylomannan: a novel TLR4 specific immunostimulator from Auricularia auricula-judae. Issue 51 (25th May 2018) - Perera, Namal; Yang, Feng-Ling; Chern, Jeffy; Chiu, Hsiao-Wen; Hsieh, Chih-Yu; Li, Lan-Hui; Zhang, Yan-Long; Hua, Kuo-Feng; Wu, Shih-Hsiung
Abstract : O -acetyl and carboxylic functionalities of Auricularia auricula-judae glucuronoxylomannan play critical roles in TLR4/MD2 receptor binding for its immunostimulatory activity. Abstract : This study established the comprehensive repeating unit structure of immunologically active glucuronoxylomannan (AAPS) from wood ear mushroom, Auricularia auricula-judae . We identified Toll-like receptor 4 (TLR4) as a critical receptor involved in AAPS-induced macrophage activation to secrete pro-inflammatory cytokines. Molecular modeling data and chemical modifications of AAPS revealed that both carboxylic and acetyl moieties of AAPS are equally essential in TLR4 binding to exert in vitro immunostimulatory activity.